Optimisation of energy efficient hybrid flowshop scheduling problem using firefly algorithm - M. F. F., Ab Rashid; Mohd Abdul, Hadi Osman (IEEE, 2020)
Hybrid Flowshop Scheduling (HFS) problem has been well studied in term of problem modelling and solution approaches. However, there were still less number of study on HFS with energy consideration. This paper proposed an optimisation scheme for energy efficient hybrid flowshop scheduling (EE-HFS) problem. In the HFS with non-identical machine capabilities, selection of machine determines the completion time and also energy utilisation. Therefore, the main issue is to assign jobs to specific machine in different stages with the purpose to minimise makespan and energy utilisation. The EE-HFS optimisation has been conducted using Firefly Algorithm (FA) on 12 benchmark HFS problem. The optimisation results indicated that the FA outperformed Ant Colony Optimisation, Particle Swarm Optimisation and Artificial Bee Colony algorithms in majority of the problems. Moreover, FA performed best in 82% of the individual optimisation objectives and achieved the fastest convergence compared with comparison algorithms.